Three-dimensional organic eutectic material and preparation method and application thereof
By using organic molecules with heteroatom-substituted adamantane and triazine ring structures, self-assembled to form organic eutectic materials, solving the problems of slow preparation speed, solvent dependence, high cost and insufficient structural diversity in the prior art, and achieving Fast, low-cost and structural diversity of organic eutectic materials.
Patent Information
- Application Number
- CN202411583667.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing preparation methods of organic eutectic materials have problems such as slow speed, solvent dependence, high cost, large energy consumption and insufficient structural diversity, which limits its large-scale commercial applications.
By using heteroatom-substituted adamantane organic molecules and triazine ring structures, organic molecules are formed by self-assembly non-covalent bonds and prepared under water system conditions, including nano and micron-sized polyhedral structures. preparation.
The rapid preparation of organic eutectic materials under the water system conditions of 0~100℃ is achieved, which avoids the problem of slow crystallization control of solvent evaporation speed, solves the dependence on organic solvents, reduces the preparation cost and energy consumption, and realizes structural diversity. The preparation of the product has environmentally friendly advantages.
Smart Images

Figure CN119390659A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of chemical technology, and specifically relates to a crystalline polyhedral structure organic eutectic material and a preparation method and application thereof. Background Art
[0002] Organic cocrystals are crystalline materials with fixed stoichiometric ratios and ordered stacking structures formed by mutual recognition and co-assembly of two or more organic molecules through intermolecular non-covalent interactions (such as pp stacking, hydrogen bonding, van der Waals forces, etc.). Their unique chemical structure, highly ordered molecular arrangement and excellent performance have attracted extensive research interest. Organic cocrystals have high photoelectric conductivity, room temperature ferroelectricity and two-photon absorption, and have broad application potential in many fields. For example, in the field of photothermal therapy and imaging, organic cocrystals can achieve efficient photothermal conversion and imaging; in the field of two-photon absorption, organic cocrystals show excellent two-photon absorption properties, providing new materials for three-dimensional fluorescence microscopy, optical information storage, etc.; organic cocrystals can also be used to prepare high-performance field effect transistors and optoelectronic devices; in the field of medicine, organic cocrystal engineering can greatly improve the solubility, bioavailability and stability of drugs while maintaining the original efficacy. Organic cocrystals have unique adjustability in molecular structure. By changing the molecular stacking mode of the original unit, the molecules can be rearranged in order, revealing the relationship between structure and properties at the molecular level, and providing a broad platform for the design and synthesis of new materials.
[0003] Organic eutectic engineering manipulates the interaction of organic molecules by selecting appropriate building blocks to produce tunable structures, morphologies, and sizes; it achieves rare and multifunctional properties through the collaborative strategy of different building blocks, demonstrating great scientific significance and practical value in the development of new functional materials. However, traditional organic eutectics are mostly assembled from planar organic small molecule donors and acceptors, usually in only two ways: columnar or staggered column stacking, and there is still a lack of structural diversity in eutectic assembly.
[0004] Compared with traditional covalent organic synthesis methods, the organic cocrystal preparation strategy provides a simple, environmentally friendly, and low-cost method for constructing non-covalent materials, avoiding complex synthesis procedures and lengthy synthesis steps. At the same time, people have made great efforts to prepare organic cocrystal materials and developed many effective methods, including mechanical grinding, solvent evaporation, recrystallization, sublimation cocrystallization, etc. However, not all methods can easily and effectively prepare organic cocrystal materials. For example, the solvent evaporation method is slow; the recrystallization method requires that the solvent has consistent solubility in the sample. For the DA-type reaction system of donor (D) and acceptor (A), the solubility of the donor and acceptor molecules is usually quite different; the sublimation cocrystal method is only suitable for substances with higher boiling points, and there are problems such as high cost, high energy consumption, and low yield. In addition, it is difficult to control the non-covalent interactions between molecules during crystal growth to a certain extent, and it is often difficult to accurately control the size and morphology of molecular crystals. These problems limit the large-scale commercial application of organic cocrystal materials to a certain extent.
[0005] Based on this, the development of organic co-crystal materials with structural diversity and their simple, low-cost preparation strategies that can be synthesized on a large scale is undoubtedly an ideal direction, but due to the challenges of selecting different compositional cooperative units, there is still little research on it. Therefore, whether from the perspective of upgrading and improving existing preparation methods or developing new methods, the development of preparation strategies for organic co-crystal materials with structural diversity is of great significance. Summary of the invention
[0006] In view of the deficiencies of the prior art, an object of the present invention is to provide a novel three-dimensional organic eutectic material.
[0007] Another object of the present invention is to provide a variety of preparation methods of the above-mentioned organic eutectic materials.
[0008] Another object of the present invention is to provide a method for controlling the crystal plane of the above-mentioned organic co-material.
[0009] The purpose of the present invention is achieved through the following technical solutions.
[0010] An organic eutectic material is formed by donor molecules and acceptor molecules through self-assembly non-covalent bonds, wherein the donor molecules are heteroatom-substituted adamantane organic molecules, and the acceptor molecules are triazine ring structure organic molecules.
[0011] In the above technical solution, in the organic eutectic material, the heteroatom-substituted adamantane organic molecule is one of urotropine, thioadamantane, and oxadamantane; the triazine ring structure organic molecule is one of cyanuric acid, melamine, and cyanuric chloride.
[0012] In the above technical solution, in the organic eutectic material, the size of the nano-organic eutectic is 100~1000 nm, and the size of the micro-organic eutectic is 1~500 µm.
[0013] In the above technical scheme, in the organic eutectic material, the organic eutectic material will form different crystal forms and morphologies due to different crystallization methods, including but not limited to: nano-organic eutectics, micron-polyhedral organic eutectics, micron-octahedral organic eutectics, micron-hexagonal organic eutectics, micron-hollow organic eutectics, micron-hexagonal organic eutectics, etc.
[0014] A method for preparing a (nano) organic eutectic material comprises the following steps: The donor molecule and the acceptor molecule are dissolved in solvents respectively (referred to as solution A and solution B), A and B are mixed to obtain a white turbid system, and an organic eutectic material can be obtained by centrifugation. The organic eutectic material is a nano-organic eutectic material.
[0015] The molar ratio of the donor molecule to the acceptor molecule is 1:1.
[0016] In the above technical solution, the solvent may be water, ethanol, DMF, methanol, DMSO, or DMAC.
[0017] In the above technical solution, the reaction temperature is 0~100°C.
[0018] A method for preparing a (micrometer) organic eutectic material comprises the following steps: The receptor molecules are dispersed in a solvent (referred to as dispersion A), dissolved after adding ammonia water, and then a fatty aldehyde solution is added. After a period of time, a white turbid system is obtained, and an organic eutectic material can be obtained by centrifugation. This material is a micron organic eutectic material.
[0019] In the above technical solution, the solvent may be water, acetonitrile, ethanol, DMF, methanol, DMSO, or DMAC.
[0020] In the above technical solution, the concentration of the dispersion is 0.01~0.5 mmol / mL.
[0021] In the above technical solution, the ratio of the ammonia molecules to the acceptor molecules is 3:1 in terms of the molar fractions.
[0022] In the above technical solution, the amount of added fatty aldehyde is 1-30 mmol.
[0023] In the above technical solution, the reaction temperature is 0~100°C.
[0024] A method for regulating the crystal plane of an organic co-material. In the above technical solution, after adding ammonia water, sodium formate, sodium acetate, sodium benzoate, formic acid or acetic acid can be introduced to change its crystal plane ratio.
[0025] The present invention provides an organic eutectic material with different crystalline polyhedral structures prepared by the method for preparing the organic eutectic material.
[0026] The organic eutectic material is used in the field of photocatalysis, and the organic eutectic material is used as an organic semiconductor for photocatalytic preparation of hydrogen peroxide.
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The method of the present invention can complete the preparation of eutectic in only 1 to 10 minutes under the condition of 0 to 100°C water system; it avoids the limitations of slow crystallization controlled by solvent evaporation rate and lengthy preparation process in traditional methods; it solves the dependence on organic solvents; it is environmentally friendly and conducive to large-scale production.
[0028] 2. The organic eutectic material designed based on eutectic engineering in the present invention can obtain hexahedral and octahedral structures with clear crystal planes and good crystallinity, thereby achieving structural diversity preparation.
[0029] 3. The method of the present invention controls crystallization through in-situ synthesis. It can solve the solubility problem of the receptor molecule, and can achieve the regulation of the structural diversity of the target product by regulating the experimental parameters. The entire preparation process is flexible and controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the structure of organic eutectic materials.
[0031] Figure 2 This is a scanning electron microscope photograph prepared in Example 1 of the present invention.
[0032] Figure 3 This is a scanning electron microscope photograph prepared in Example 2 of the present invention.
[0033] Figure 4 This is a scanning electron microscope photograph prepared in Example 3 of the present invention.
[0034] Figure 5 This is a scanning electron microscope photograph prepared in Example 4 of the present invention.
[0035] Figure 6 This is the X-ray diffraction curve of the powder prepared in Example 2 of the present invention.
[0036] Figure 7 It is the X-ray diffraction curve of the powder prepared in Example 4 of the present invention.
[0037] Figure 8 This is a scanning electron microscope photograph prepared in Example 5 of the present invention.
[0038] Fig. 9 This is a scanning electron microscope photograph prepared in Example 6 of the present invention.
[0039] Fig.10 This is a scanning electron microscope photograph prepared in Example 7 of the present invention.
[0040] Fig.11 The photocatalytic synthesis of hydrogen peroxide performance of the organic co-crystals prepared in Examples 2 and 3.
[0041] Fig.12 The natural light photocatalytic synthesis of hydrogen peroxide performance of the organic co-crystal prepared in Example 3. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0043] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art. Example 1
[0044] Preparation of Nano-Organic Cocrystals At room temperature, 0.177 g of thiocyanate was dissolved in 20 mL of ethanol, and 0.140 g of hexamethylenetetramine (urotropine) was dissolved in 20 mL of deionized water. The two solutions were mixed and instantly turned into a white turbid system. White precipitates were obtained by centrifugation. The precipitates were washed three times with ethanol and deionized water respectively, and dried in an oven at 60°C.
[0045] The scanning electron microscopy of the organic eutectic material in Example 1 is as follows Figure 2 As shown in the figure, it can be seen that its size is nanometer-level and its shape is octahedral. Example 2
[0046] Preparation of micron octahedral organic eutectics At room temperature, 0.177 g of trithiocyanuric acid was dispersed in 10 mL of deionized water, and 500 μL of ammonia water was added, followed by 2 mL of formaldehyde solution. After 30 seconds, the system turned into a white turbid system, which was centrifuged to obtain a white precipitate. The system was washed three times with ethanol and deionized water, and then dried in an oven at 60°C.
[0047] The scanning electron microscopy of the organic eutectic material in Example 2 is as follows Figure 3 As shown in the figure, it can be seen that its morphology is a micron-sized octahedron with a size between 2 and 10 µm; from the powder X-ray diffraction curve ( Figure 6 ) It can be seen that it has a high degree of crystallinity. Its crystallization mode is a trigonal system with a space group of R3, and the unit cell parameters are about a=9.7700, b=9.7700, c=25.7744, a=90, b=90, c=120. Its crystal structure is as follows Figure 1 (Right) The trigonal unit cell is shown. Example 3
[0048] Preparation of micron hexahedral organic eutectics At room temperature, 0.177 g of trithiocyanuric acid was dispersed in 30 mL of deionized water, and 500 µL of ammonia water was added, followed by 2 mL of formaldehyde solution. The system turned into a white turbid system after 1 min, and a white precipitate was obtained by centrifugation. The system was washed three times with ethanol and deionized water in turn, and dried in an oven at 60 °C.
[0049] The scanning electron microscopy of the organic eutectic material in Example 3 is as follows Figure 4 As shown in the figure, it can be seen that its morphology changes from octahedron to hexagonal. Example 4
[0050] Preparation of micron-polyhedral organic eutectics At room temperature, 0.177 g of trithiocyanuric acid was dispersed in 10 mL of deionized water, 500 µL of ammonia water was added, the mixture was filtered with a 0.22 µm syringe filter, and then 500 µL of sodium formate solution (5.3 M) was added, followed by 200 µL of formaldehyde. The mixture was placed in a constant temperature oven at 80 °C for 8 h, and the transparent micron organic eutectic was obtained by centrifugation. The mixture was washed three times with ethanol and deionized water in sequence, and dried in an oven at 60 °C.
[0051] The scanning electron microscopy of the organic eutectic material in Example 4 is as follows Figure 5 As shown in the figure, it can be seen that its morphology is polyhedral and its size is >100 µm; its crystal structure and crystallinity can be seen from the powder X-ray diffraction curve ( Figure 7 ). It has high crystallinity, and its crystallization mode is hexagonal system with space group P 163 mc, and the unit cell parameters are about a=9.6534, b=9.6534, c=16.438, a=90, b=90, c=120. Its crystal structure is as follows Figure 1 (Left) The trigonal unit cell is shown. Example 5
[0052] Large-scale preparation of micronized octahedral organic cocrystals At room temperature, 17.7 g of thiocyanuric acid was dispersed in 1000 mL of deionized water, and 50 mL of ammonia water was added, followed by 200 mL of formaldehyde solution. After 30 s, the system turned into a white turbid system. The white precipitate was obtained by centrifugation. The system was washed three times with ethanol and deionized water in turn, and dried in an oven at 60°C.
[0053] The scanning electron microscopy of the organic eutectic material in Example 5 is as follows Figure 8 shown. Example 6
[0054] Preparation of micron hollowed-out organic eutectics At room temperature, 0.177 g of trithiocyanuric acid was dispersed in 10 mL of methanol, 500 µL of ammonia water was added, and then 2 mL of formaldehyde solution was added. After 2 min, the system turned into a white turbid system, and a white precipitate was obtained by centrifugation. The system was washed three times with ethanol and deionized water in sequence.
[0055] The scanning electron microscopy of the organic eutectic material in Example 6 is as follows Fig. 9 As shown in the figure, it can be seen that its shape has changed into a hollow octahedron. Example 7
[0056] Preparation of micron hexagonal pyramidal organic eutectics At room temperature, 0.177 g of trithiocyanuric acid was dispersed in 10 mL of deionized water, and 500 µL of ammonia water and 3 mL of sodium formate solution (5.3 M) were added. Then, 2 mL of formaldehyde solution was added. The system turned into a white turbid system after 2 min. The white precipitate was obtained by centrifugation and washed three times with ethanol and deionized water in sequence.
[0057] The scanning electron microscopy of the organic eutectic material in Example 7 is as follows Fig.10 As shown in the figure, it can be seen that its morphology has changed into a hexagonal pyramid. Example 8
[0058] 15 mg of the micron octahedral organic cocrystal prepared in Example 2 was dispersed in 35 mL of benzyl alcohol / water solution (v / v: 1 / 6), and the mixture was stirred for 30 min in a dark place with air bubbles. A photocatalytic reaction was carried out with a 300 W xenon lamp as the light source (λ >300 nm and λ >400 nm), and the reaction solution was collected. The H2O2 concentration was determined by coloring method (potassium titanium oxalate was used as the color developer, 1 mL of the reaction solution, 1 mL of 3 M sulfuric acid and 1 mL of 0.05 M titanium oxalate solution were taken for color development, and the absorbance of the color development solution was detected by UV-visible spectrophotometer). The results are as follows: Fig.11 As shown in Figure 2, in the wavelength band of λ > 400 nm, the hydrogen peroxide yield reached 25.15 mmol g -1 h -1The apparent quantum efficiency at 400 nm is 11.3%; in the wavelength range of λ > 300 nm, the hydrogen peroxide yield is 37.13 mmol g -1 h -1 . Example 9
[0059] 15 mg of the micron hexahedral organic eutectic prepared in Example 3 was dispersed in 35 mL of benzyl alcohol / water solution (v / v: 1 / 6), and the mixture was stirred for 30 min in a dark place with air bubbles. A photocatalytic reaction was carried out with a 300 W xenon lamp as the light source (λ >300 nm and λ >400 nm), and the reaction solution was collected. The H2O2 concentration was determined by coloring method (potassium titanium oxalate was used as the color developer, 1 mL of the reaction solution, 1 mL of 3 M sulfuric acid and 1 mL of 0.05 M titanium oxalate solution were taken for color development, and the absorbance of the color development solution was detected by UV-visible spectrophotometer). The results are as follows: Fig.11 As shown in Figure 2, in the wavelength band of λ > 400 nm, the hydrogen peroxide yield reached 27.35 mmol g -1 h -1 The apparent quantum efficiency at 400 nm was 17.3%; in the wavelength range of λ > 300 nm, the hydrogen peroxide yield reached 45.27 mmol g -1 h -1 . Example 10
[0060] 15 mg of the micron hexahedral organic eutectic prepared in Example 3 was dispersed in 35 mL of benzyl alcohol / water solution (v / v: 1 / 6), and the mixture was stirred for 30 min in a dark place with air bubbles. The photocatalytic reaction was carried out using outdoor sunlight as the light source, and the reaction solution was collected and analyzed. The H2O2 concentration was determined by coloring method (potassium titanium oxalate was used as the color developer, 1 mL of the reaction solution, 1 mL of 3 M sulfuric acid and 1 mL of 0.05 M titanium oxalate solution were taken for color development, and the absorbance of the color development solution was detected by UV-visible spectrophotometer). The results are as follows: Fig.12 As shown in Figure 2, under natural light, without stirring or continuous air flow, the hydrogen peroxide yield can still reach 26.95 mmol g -1 h -1 , indicating that the material has high practical production value.
Claims
1. A three-dimensional organic eutectic material, characterized in that: It is formed by a donor molecule and an acceptor molecule through self-assembly non-covalent bonds; the donor molecule is a heteroatom-substituted adamantane organic molecule, and the acceptor molecule is an organic molecule with a triazine ring structure; the heteroatom-substituted adamantane organic molecule is one of urotropine, thioadamantane, and oxaadamantane; the organic molecule with a triazine ring structure is one of thiocyanuric acid, melamine, and cyanuric chloride.
2. The organic eutectic material according to claim 1, characterized in that: The organic eutectic material is a nano-organic eutectic material or a micro-organic eutectic material. The size of the nano-organic eutectic is 100-1000 nm, and the size of the micro-organic eutectic is 1-500 µm.
3. The organic eutectic material according to claim 1, characterized in that: The organic eutectic material has the following crystal forms: nano-organic eutectic, micron-polyhedral organic eutectic, micron-octahedral organic eutectic, micron-hexagonal organic eutectic, micron-hollow organic eutectic, and micron-hexagonal pyramidal organic eutectic.
4. The method for preparing the organic eutectic material according to claim 1, characterized in that: The following steps are involved: The donor molecule and the acceptor molecule are dissolved in solvents, respectively, which are recorded as solution A and solution B. Solution A and solution B are mixed to obtain a white turbid system, and the organic eutectic material is obtained by centrifugation.
5. The preparation method according to claim 4, characterized in that: The solvent is water, ethanol, DMF, methanol, DMSO, DMAC; the reaction temperature is 0-100°C.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the donor molecule to the acceptor molecule is 1:
1.
7. The method for preparing the organic eutectic material according to claim 1, characterized in that: The following steps are involved: The receptor molecules are dispersed in a dispersion solvent, which is referred to as dispersion A; Ammonia water was added to dissolve, and then aliphatic aldehyde solution was added to obtain a white turbid system, which was centrifuged to obtain an organic eutectic material.
8. The preparation method according to claim 7, characterized in that: The dispersion solvent is water, acetonitrile, ethanol, DMF, methanol, DMSO, and DMAC; the concentration of the dispersion A is 0.001-0.5 mmol / mL; the molar ratio of the ammonia molecules to the acceptor molecules is 3:1 in terms of molar fractions; the amount of the added fatty aldehyde is 1-30 mmol; and the reaction temperature is 0-100°C.
9. The preparation method according to claim 7, characterized in that: After adding ammonia water, add sodium formate, sodium acetate, sodium benzoate, formic acid or acetic acid.
10. The use of the organic eutectic material according to claim 1, characterized in that: The organic eutectic material is applied in the field of photocatalysis, and the organic eutectic material is used as an organic semiconductor for photocatalytic preparation of hydrogen peroxide.
Citation Information
Patent Citations
Organic eutectic material and preparation method and application thereof
CN114702496A
Organic room-temperature phosphorescent eutectic material and preparation method thereof
CN115433567A
High-crystallinity carbon nitride based on cyanuric acid-lithium chloride eutectic and preparation method thereof
CN115608401A
Design, preparation and application of efficient organic light-emitting eutectic
CN115651021A